Safety and Comfort of Environmental Settings for The Elderly in Semampir Utara Settlement, Surabaya - Nurilla Rojabia, Izza; Argarini, Tri Okta; Amelia, Nonny Rifka Rizky (Program Studi Arsitektur, Fakultas Teknik, Universitas Katolik Parahyangan, 2025)
East Java has the largest elderly population in the country. This presents a challenge, requiring special treatment, particularly in terms of environmental comfort and safety. One factor influencing a settlement is the development of road infrastructure in Surabaya, which has impacted surrounding settlements, such as the Semampir Utara Settlement. This settlement is a modest slum, so the quality of the environmental setting needs to be questioned, especially in terms of accommodating elderly activities. This study aims to identify comfort and security factors as one aspect of the quality of the environmental setting in accommodating elderly activities in the settlement. This study is a qualitative study using a snowball sampling method reinforced by triangulation to combine various sources of information from elderly people, families, and surrounding community groups to ensure consistent perspectives on environmental quality and elderly activities. Thematic analysis was used in this study to identify several factors related to comfort and security in elderly activity patterns, namely memory, social support, passive interaction, and noise.